Patient engagement in the design of an intervention to prevent muscle loss in individuals with knee osteoarthritis and a body mass index (BMI) ≥ 35. (20th December 2021) - Godziuk, Kristine; Prado, Carla M.; Forhan, Mary
Abstract: Objective: Interventions for knee osteoarthritis (OA) in adults with a large body size (defined as a body mass index [BMI] ≥ 35 kg/m 2 ) often prioritise weight‐loss, which may overshadow specific benefits for physical function, metabolic health, and body composition. As part of the development of a future clinical study, we gathered perspectives from individuals living with knee OA and a large body size to inform the proposed intervention design and delivery. Methods: Purposive and voluntary sampling was used to engage individuals ≥40 years of age with self‐reported knee OA and a BMI ≥ 35 kg/m 2 . An anonymous electronic survey was distributed on social media between April 2020 and June 2020. Open‐ended questions addressed a proposed 12‐week multimodal intervention (involving targeted nutrition, resistance exercises, and self‐management support). An optional semi‐structured interview was offered upon completion, with interviews recorded and transcribed verbatim. Reflexive thematic analysis and interpretation guided by an acceptability framework was used to identify recommendations for the intervention design and delivery. Results: Twenty individuals living across Canada completed the survey (100% female; 18 aged <65 years and 2 ≥ 65 years). Ten individuals completed the interview. From aggregate survey and interview data, three recommendations were generated: (1) the effectiveness of the intervention for health improvement (specifically mobility and pain) must be emphasised to avoid perceived weight‐loss expectations; (2) extend support beyond 12‐weeks and consider terminology free from weight‐bias to enhance acceptance; (3) include optional customisation of intervention delivery to reduce acceptability‐related burden. Conclusion: These female patient‐derived recommendations may improve perceived intervention acceptability, and thereby may enhance participant enrolment and retention in clinical trials.